Unusual first record of Torpedo puelcha (Chondrichthyes, Torpedinidae) in an Argentinean coastal lagoon - Belleggia, Mauro (2008)
One specimen of Torpedo puelcha was recorded for the first time in a coastal lagoon. Morphometric characteristics were provided together with the analysis of sexual maturity and stomach contents. The presence of this specimen is most likely due to accidental introduction.